2013
DOI: 10.1136/bmjqs-2012-001615
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of diagnostic error in medicine

Abstract: A wide variety of research studies suggest that breakdowns in the diagnostic process result in a staggering toll of harm and patient deaths. These include autopsy studies, case reviews, surveys of patient and physicians, voluntary reporting systems, using standardised patients, second reviews, diagnostic testing audits and closed claims reviews. Although these different approaches provide important information and unique insights regarding diagnostic errors, each has limitations and none is well suited to esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
355
1
11

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 503 publications
(378 citation statements)
references
References 58 publications
(33 reference statements)
11
355
1
11
Order By: Relevance
“…A variety of methods and data sources have been used to establish incidence (e.g. autopsies, medical records, diagnostic testing audits, case reviews, malpractice claims, and voluntary reports from patients and clinicians) [1,10]. Unique insights can be gleaned from each data source; however, limitations of each preclude the possibility of deriving broader population-based estimates or ranges of diagnostic error on a national scale.…”
Section: Measurement Methodsmentioning
confidence: 99%
“…A variety of methods and data sources have been used to establish incidence (e.g. autopsies, medical records, diagnostic testing audits, case reviews, malpractice claims, and voluntary reports from patients and clinicians) [1,10]. Unique insights can be gleaned from each data source; however, limitations of each preclude the possibility of deriving broader population-based estimates or ranges of diagnostic error on a national scale.…”
Section: Measurement Methodsmentioning
confidence: 99%
“…Recent studies harness the power of electronic health records (EHRs) by using "triggers" to filter data into subsets enriched with cases of diagnostic error, through selecting cases considered at higher risk for such errors [9][10][11][12][13][14]. By applying these screens to ambulatory EHRs they increased the prevalence of cases of error from 2.1% at baseline to 5.4%-20.9% in groups using screening triggers such as an unexpected return visit or hospitalization.…”
Section: Introductionmentioning
confidence: 99%
“…This last barrier limits the extensive review of records in research, with one study of diagnostic errors reporting a mean review time of 1.4 hours per record [5]. An ED based study found that 86% of the diagnostic error uncovered were preventable, suggesting that errors of this nature could be reduced significantly, if not eliminated [10].Recent studies harness the power of electronic health records (EHRs) by using "triggers" to filter data into subsets enriched with cases of diagnostic error, through selecting cases considered at higher risk for such errors [9][10][11][12][13][14]. By applying these screens to ambulatory EHRs they increased the prevalence of cases of error from 2.1% at baseline to 5.4%-20.9% in groups using screening triggers such as an unexpected return visit or hospitalization.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…One analysis concludes that "while the exact prevalence of diagnostic error remains unknown, data from autopsy series spanning several decades conservatively and consistently reveal error rates of 10%-15%" (Schiff et al, 2009(Schiff et al, : 1881. Since autopsies are rare in many countries other methods of tracking diagnostic error rates have had to be employed but the overall picture is the same: diagnostic error is relatively common (Kuhn, 2002;Graber, 2013;Singh et al, 2013).…”
mentioning
confidence: 99%